Geothermal power plants around the world. A sourcebook on the production of electricity from geothermal energy, draft of Chapter 10 - DiPippo, R. (Southeastern Massachusetts Univ., North Dartmouth (USA), 1979)
This report constitutes a consolidation and a condensation of several individual topical reports dealing with the geothermal electric power stations around the world. An introduction is given to various types of energy conversion systems for use with geothermal resouces. Power plant performance and operating factors are defined and discussed. Existing geothermal plants in the following countries are covered: China, El Salvador, Iceland, Italy, Japan, Mexico, New Zealand, the Philippines, Turkey, the Union of Soviet Socialist Republics, and the United States. In each case, the geological setting is outlined, the geothermal fluid characteristics are given, the gathering system, energy conversion system, and fluid disposal method are described, and the environmental impact is discussed. In some cases the economics of power generation are also presented. Plans for future usage of geothermal energy are described for the above-mentioned countries and the following additional ones: the Azores (Portugal), Chile, Costa Rica, Guatemala, Honduras, Indonesia, Kenya, Nicaragua, and Panama. Technical data is presented in twenty-two tables; forty-one figures, including eleven photographs, are also included to illustrate the text. A comprehensive list of references is provided for the reader who wishes to make an in-depth study of any of the topics mentioned.